algebra

posted by .

Simplify.

2x^3-2x
________
7x^3-14x^2+7x

  • algebra -

    = 2x(x^2 - 1)/( 7x(x^2 - 2x +1)
    = 2x(x-1)(x+1)/(7x(x-1)(x-1))
    = 2(x+1)/(7(x-1))
    or
    (2x+2x)/(7x - 7) , x ≠ 1

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math - Derivatives

    Differentiate the given function. Simplify the answer. f(x) = 28x*ln√x + 42 f'(x) = 28*ln(x)^(1/2) + (1/(x^(1/2))*(1/2(x)^(-1/2)28x) f'(x) = 28*ln(x)^(1/2) + (14x*x^(-1/2))/x^(1/2) f'(x) = 28*ln(x)^(1/2) + (14x^(-1/2))/x^(1/2) …
  2. math

    which equation is equivalent to 5x-2(7x+1)=14x?
  3. algebra

    i cannot figure any of this stuff out. please help. if you can there are 15 more of these... 1. Simplify 5 + (7-1)2/6 A11 B41/6 C51/6 D7 E17/6 F23 2. Simplify (26/2 + 33)/(23) A11/3 B5 C20/3 D8 E6 F131/8 3. Simplify [7+2(5 - 9)2]/[(4+1)2 …
  4. algebra... help soon please

    i cannot figure any of this stuff out. please help. if you can there are 15 more of these... 1. Simplify 5 + (7-1)2/6 A11 B41/6 C51/6 D7 E17/6 F23 2. Simplify (26/2 + 33)/(23) A11/3 B5 C20/3 D8 E6 F131/8 3. Simplify [7+2(5 - 9)2]/[(4+1)2 …
  5. algebra

    solve the following equation by clearing fraction want to know if this right -7/3-5/2x=8+2x 6(-7/3)-(5/2)(6)=6(6)+2x(6) 14x-15=48+12x 14x-12x-15=48+14x-14x 2x-15=48 2x-15+15=48+15 2x=-33 2x/2x=-33/2 x=-33/2
  6. algebra

    solve the following equation by clearing fractions show all work want to know if this right -7/3-5/2x=8+2x 6(-2/3)-(5/2x)(6)=6(8)+2x(6) 14x-15=48+12x 14x-12x-15=48+14x-14x 2x-15=48 2x-15+15=48+14x-14x 2x-15=48 2x-15+15=48+15 2x=-33 …
  7. Algebra

    Solve and simplify: x^2+14x-4=0
  8. Maths

    find the equation of the perpendicular bisector of the line joining P(2, -4) to Q(-5,1) A. 8y-14x 13=0 B. 8y-14x-13=0 C. 8y 14x-13=0 D. 8y 14x 13=0 Please I need someone to help me with this, with an explanatory workings.
  9. algebra

    Simplify -14x^3/x^3 - 5x^4 it too hard for me to understand
  10. Algebra

    Really need some help 1. 14x^2+4+3x-12x^2-3+11x A) 2x^2+7x+1 B) 2x^2+14x+1 C) 2x^2+14x+7 D) 26x^2+7x+7 2. 4x^2+4-5x+x-2x^2+8 A) -2x^2+4x+12 B) -2x^2-4x+12 C) 2x^2+4x+12 D) 2x^2-4x+12

More Similar Questions